1991
DOI: 10.1111/j.1469-8749.1991.tb05089.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Race and Gender on Neurological Level Myelomeningocele

Abstract: SUMMARY The association of race and gender with different neurological levels of myelomeningocele was studied in 251 patients. Over‐all, the white to black ratio was 3·6 and the male to female ratio was 0·86. However, the proportions of whites and females were significantly increased in thoracic‐level patients (white to black ratio 13·6, male to female ratio 0·43), whereas the lumbar‐level patients had sex and white to black ratios equivalent to the area population. This supports the concept that thoracic‐leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
(22 reference statements)
1
6
0
3
Order By: Relevance
“…Several studies have assessed spina bifida lesion level and race/ethnicity, and have not identified consistent associations [Greene et al, 1991; Shaw et al, 1994; Shaw et al, 2000; Au et al, 2008; Mitchell, 2008]. However, many of these studies either were not population‐based or used less specific categories of lesion level (e.g., high vs. low) than the present study.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have assessed spina bifida lesion level and race/ethnicity, and have not identified consistent associations [Greene et al, 1991; Shaw et al, 1994; Shaw et al, 2000; Au et al, 2008; Mitchell, 2008]. However, many of these studies either were not population‐based or used less specific categories of lesion level (e.g., high vs. low) than the present study.…”
Section: Discussionmentioning
confidence: 60%
“…There is also evidence that the clinical and demographic characteristics associated with AN and SB have changed as the prevalence declined. Both AN and SB have been observed more frequently at birth in females than in males (Khoury et al, 1982; Sever, 1982; Dolk et al, 1991; Greene et al, 1991; Elwood et al, 1992; Yen et al, 1992), and among whites than among blacks or African Americans, with the highest prevalence among those of Hispanic or Latino ethnicity (Canfield et al, 1996; 2006; Shaw et al, 1997; Williams et al, 2005). Analyzing data from 1968 to 1989 using the Birth Defects Monitoring Program and the Metropolitan Atlanta Congenital Defects Program (MACDP), Yen et al (1992) showed that the prevalence of AN and SB was decreasing more rapidly in the U.S. among females, whites, those in whom AN or SB was the only defect, and those who lived in the eastern part of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing data from 1968 to 1989 using the Birth Defects Monitoring Program and the Metropolitan Atlanta Congenital Defects Program (MACDP), Yen et al (1992) showed that the prevalence of AN and SB was decreasing more rapidly in the U.S. among females, whites, those in whom AN or SB was the only defect, and those who lived in the eastern part of the country. This suggests that AN and SB are etiologically heterogeneous, that the relative contribution of environmental and genetic factors can differ for different segments of the population, and that the characteristics associated with AN and SB can vary depending on their overall prevalence (high vs. low) (Khoury et al, 1982; Sever, 1982; Dolk et al, 1991; Greene et al, 1991; Yen et al, 1992; Wyszynski, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Bu oran literatürle uyumludur (8). Toplamda cinsiyet dağılımına baktığımız zaman literatürle uyumlu olarak bu çalışmada da kız çocuklarında daha fazla görüldüğü tespit edilmiştir (9). Meningosel hastaları tek başına incelediğinde ise cinsiyet dağılımında eşitlik olduğu görüldü.…”
Section: Discussionunclassified
“…Meningosel hastaları tek başına incelediğinde ise cinsiyet dağılımında eşitlik olduğu görüldü. Literatürde bazı çalışmalarda belirgin cinsiyet farkı saptanmamış olsa da bir çok çalışmada kız hakimiyeti rapor edilmiştir (8,9). Çalışmada alt ekstremitede nörolojik defisiti en sık meningomyeloselli hastalarda tespit ettik.…”
Section: Discussionunclassified